2013
DOI: 10.1124/dmd.113.052993
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Mouse Hepatic CYP3A Protein by 3-Methylcholanthrene Does Not Require Cytochrome P450-Dependent Metabolism

Abstract: The aryl hydrocarbon receptor (AHR)-dependent induction of cytochromes P450 (P450) such as CYP1A1 by 3-methylcholanthrene (MC) and related polycyclic aromatic hydrocarbons is well characterized. We reported previously that MC treatment triggers a pronounced downregulation, particularly at the protein level, of mouse hepatic Cyp3a11, a counterpart of the key human drug-metabolizing enzyme CYP3A4. To determine whether this effect of MC requires hepatic microsomal P450 activity, we studied liver Cpr-null (LCN) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, one cannot exclude that SLC16A1 expression could also be modulated by direct interactions between PXR and other cofactors. For instance, it was previously shown that interaction of PXR with AhR could regulate the basal level of CYP3A4 expression and its activation by PXR agonists both in vitro and in vivo [ 51 , 52 , 53 ]. It was also demonstrated that both AhR and PXR could regulate the expression of UGT1A1 by binding to different promotor regions of this PXR target gene [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, one cannot exclude that SLC16A1 expression could also be modulated by direct interactions between PXR and other cofactors. For instance, it was previously shown that interaction of PXR with AhR could regulate the basal level of CYP3A4 expression and its activation by PXR agonists both in vitro and in vivo [ 51 , 52 , 53 ]. It was also demonstrated that both AhR and PXR could regulate the expression of UGT1A1 by binding to different promotor regions of this PXR target gene [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incubations were done in triplicates and repeated once. The same assay kit has previously been used to measure mouse Cyp3a activity (Lee et al, 2013;Selwyn et al, 2015;Li et al, 2017).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Male and female humanized PXR-CAR-CYP3A4/3A7 mice were exposed to MC under conditions previously shown to downregulate hepatic Cyp3a11 expression and activity in male wild-type C57BL/6 mice (Lee et al, 2006(Lee et al, , 2013a. MC treatment had minimal effects on the liver to body weight ratio, with a 25% increase seen at 72 hours postdosing only in females (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Studies of the regulation of the major CYP3A4 counterpart in mice (Cyp3a11) by 3-methylcholanthrene (MC), a model PAH that is readily biotransformed by P450s (Riddick et al, 1994), have provided valuable insight. Our laboratory showed a pronounced loss of mouse hepatic Cyp3a11 protein triggered by MC treatment (Lee et al, 2006) and subsequently established that the suppression of Cyp3a11 mRNA and protein caused by MC is comparable in wild-type and liver Cpr-null mice that are nearly devoid of hepatic microsomal P450 activity due to hepatocyte-specific conditional deletion of NADPH-cytochrome P450 oxidoreductase (Lee et al, 2013a). Thus, MC appears to downregulate mouse hepatic Cyp3a11 via a pretranslational mechanism that does not require hepatic microsomal P450-dependent activity.…”
Section: Introductionmentioning
confidence: 93%